2021
DOI: 10.3389/fmars.2021.619190
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Post-release Mortality: Inferences on Recovery Periods and Natural Mortality From Electronic Tagging Data for Discarded Lamnid Sharks

Abstract: Accurately characterizing the biology of a pelagic shark species is critical when assessing its status and resilience to fishing pressure. Natural mortality (M) is well known to be a key parameter determining productivity and resilience, but also one for which estimates are most uncertain. While M can be inferred from life history, validated direct estimates are extremely rare for sharks. Porbeagle (Lamna nasus) and shortfin mako (Isurus oxyrinchus) are presently overfished in the North Atlantic, but there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Despite a low sample size, we also revealed that recovery times increased as shark length decreased. Although physiological stress responses to capture (e.g., lactate accumulation) are known to be magnified in smaller individuals for some shark species, which can influence postrelease outcomes (Gallagher et al, 2014;Talwar et al, 2017;Bowlby et al, 2021), white sharks across a range of sizes are quite physiologically resilient to short captures (<75 min, as per our study; Gallagher et al, 2019;Tate et al, 2019). Therefore, other factors (e.g., size-specific personalities) may underlie the 10-fold variance in behavioral recovery (∼3-30 h) we observed across sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a low sample size, we also revealed that recovery times increased as shark length decreased. Although physiological stress responses to capture (e.g., lactate accumulation) are known to be magnified in smaller individuals for some shark species, which can influence postrelease outcomes (Gallagher et al, 2014;Talwar et al, 2017;Bowlby et al, 2021), white sharks across a range of sizes are quite physiologically resilient to short captures (<75 min, as per our study; Gallagher et al, 2019;Tate et al, 2019). Therefore, other factors (e.g., size-specific personalities) may underlie the 10-fold variance in behavioral recovery (∼3-30 h) we observed across sizes.…”
Section: Discussionmentioning
confidence: 99%
“…So far, daily diary tags have been used to reveal many aspects of aquatic animals' natural behaviors including foraging activities, cost-efficient movement strategies, and habitat use (Shepard et al, 2011;Benoit-Bird et al, 2013;Andrzejaczek et al, 2019a). By contrast, applied behavioral research on disturbances following capture in marine and terrestrial systems has mostly relied on either traditional biotelemetry, pop-up time-depth archival tags, or accelerometers (Afonso and Hazin, 2014;Rode et al, 2014;Barnes et al, 2016;Becciolini et al, 2019;Bowlby et al, 2021;Shuert et al, 2021). However, biotelemetryderived movements or depth profiles are often insufficient for resolving cryptic behavioral processes (e.g., foraging and resting) relevant to recovery, especially in aquatic systems where telemetry data are particularly intermittent and coarse (Andrzejaczek et al, 2018(Andrzejaczek et al, , 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…For sharks that survive capture and tagging, electronic tags can evaluate swimming performance metrics that may be related to behavioral changes following release. Irregular dive behavior consists of inconsistent or restricted depth use [ 33 35 ], increased tailbeat frequencies and elevated overall dynamic body acceleration (ODBA) [ 28 ], and reduced frequency and amplitude of dives resulting in a diminished dive variance [ 36 , 37 ]. Quantifying these changes over time allows for a recovery period to be estimated as the amount of time it takes for an individual to restore normal values for these swimming performance metrics.…”
Section: Methodsmentioning
confidence: 99%
“…The noncapture methodology was preferred to minimize tagging effects and ensure that movement data were more likely to represent natural behaviour. Tagging onboard following capture is known to alter movement behaviour during a prolonged recovery period for lamnid sharks (Hoolihan et al 2011;Bowlby et al 2021) and carcharhinid species (Vaudo et al 2014). Also, our non-capture tagging methodology was unaffected by gear selectivity, unlike capture-based sampling that is known to be size-selective (Maunder et al 2006;Rotherham et al 2007;Christiansen et al 2020).…”
Section: Tagging Methodologymentioning
confidence: 99%
“…Water temperature becomes a key environmental variable because it is both recorded by PSAT tags and is one of the most readily available oceanographic covariates to evaluate (Fourcade et al 2018). Typically, PSAT data collected throughout ocean basins are aggregated to increase sample size (e.g., Bowlby et al 2021) and longer-term deployments are considered optimal (Sippel et al 2015). However, our comparisons show that the distribution of temperatures experienced by white sharks during seasonal movements to Canadian waters is significantly narrower than those experienced at the same times of year in the US and differs markedly from other times of the year.…”
Section: Conservation Implicationsmentioning
confidence: 99%